Factors affecting germination of Araucaria araucana (Araucariaceae) seeds from the xeric forest - Duplancic, María Andrea; Martínez Carretero, Eduardo; Cavagnaro, Bruno; Herrera Moratta, Mario; Navas Romero, Ana Laura (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
A. araucana is a dioecious conifer endemic of Argentina and Chile. Female trees produce large seeds that are dispersed between February and May. Some aspects on the self-ecology of this species, particularly in the xeric forest and in its eastern border of distribution, remain yet under study. The objectives of this study were to evaluate the effect of temperature and pre-germinative treatments on germination of A. araucana seeds from the xeric forest. Temperature effect was assessed in growth chambers considering six temperatures levels from 10ºC to 35ºC, with intervals of 5ºC. Cardinal minimum, maximum and optimal germination temperatures were 15ºC, 30ºC and 25ºC, respectively. Pre-germinative treatment effect was assessed considering five treatments: imbibition, complete mechanical scarification, partial mechanical scarification, chemical scarification and control. The use of pre-germinative treatments doubled the percentage of germination as regards the reference control. To maximize the germination of seeds of A. araucana is recommended the use of a pre-germinative treatment of imbibition in distilled water and incubate the seeds at 25ºC.